Engineered cysteine antibodies: an improved antibody-drug conjugate platform with a novel mechanism of drug-linker stability. Issue 2 (23rd January 2018) - Sussman, D; Westendorf, L; Meyer, D W; Leiske, C I; Anderson, M; Okeley, N M; Alley, S C; Lyon, R; Sanderson, R J; Carter, P J; Benjamin, D R
Abstract: Antibody-drug conjugates (ADCs) are fulfilling the promise of targeted therapy with meaningful clinical success. An intense research effort is directed towards improving pharmacokinetic profiles, toxicity and chemical stability of ADCs. The majority of ADCs use amide and thioether chemistry to link potent cytotoxic agents to antibodies via endogenous lysine and cysteine residues. While maleimide-cysteine conjugation is used for many clinical stage ADC programs, maleimides have been shown to exhibit some degree of post-conjugation instability. Previous research with site-directed mutagenic incorporation of cysteine residues for conjugation revealed that the stability of the drug-antibody linkage depends on the site of conjugation. Here we report on a collection of engineered cysteine antibodies (S239C, E269C, K326C and A327C) that can be site-specifically conjugated to potent cytotoxic agents to produce homogenous 2-loaded ADCs. These ADCs confirm that site of conjugation impacts maleimide stability and present a novel mechanism of thioether stabilization, effectively unlinking stability from either local chemical environment or calculated solvent accessibility and expanding the current paradigm for ADC drug-linker stability. These ADCs show potent in vitro and in vivo activity while delivering half of the molar equivalent dose of drug per antibody when compared to an average 4-loaded ADC. In addition, our lead engineered site shields highly hydrophobic drugs, enabling conjugation, formulation and clinical use of otherwise intractable chemotypes.